Prevalence of text neck syndrome among Iraqi medical students: a cross-sectional study - Kadhim Rashid, Muayad; Ali Jadoo, Saad Ahmed; Hassan Alhusseiny, Adil; Ibrahim Latif, Ismail (Journal of Ideas in Health, 2022)
Background: Excessive use of portable electronic devices causes neck flexion and the emergence of text neck syndrome (TNS). This study aims to explore the prevalence of TNS among medical students during the COVID-19 lockdown in Iraq. Methods: A prospective cross-sectional web-based study was conducted from 1st to 20th March 2021 at the faculty of medicine, Diyala University, Iraq. A self-administered questionnaire was distributed among the medical students using Google Form through social media (WhatsApp group). The semi-structured questionnaire included the sociodemographic, the valid smartphone addiction scale-short version (SAS-SV), and the neck disability index (NDI). Univariate, bivariate, and multiple logistic regression were used to analyze the data. SPSS version 16. The statistical significance is considered at less than 0.05. Results: Out of 273 medical students included in the study, 59.3% were males, unmarried (88.3%), and from the 1st year (21.6%). The mean age of students was 21.27 ± 1.74 years. The prevalence of text neck syndrome was 64.5%. About two-thirds (61.5%) of students were addicted to their smartphones and used them more than five h/daily (63.7%). Factors associated with neck disability were the students who did not warm up neck muscles before using the smartphone (OR = 8.796, 95% CI: 1.724 to 24.884), addicted to the smartphone (OR = 6.803, 95% CI: 3.455 to 13.397), experienced increase in daily hours using the smartphone during the COVID-19 related quarantine (OR = 5.370, 95% CI: 2.523 to 11.427), maintained smartphone use five hours and more daily (OR = 2.818, 95% CI: 1.422 to 5.587), had neck pain (OR = 2.876, 95% CI: 1.356 to 6.098), the female gender (OR = 2.756, 95% CI: 1.221 to 6.221), and those who did not have a frequent break when using the smartphone (OR = 2.693, 95% CI: 1.329 to 5.454). Conclusion: In conclusion, the prevalence of neck disability was high among the surveyed medical students. Addiction and excessive smartphone use with a lack of attention to warm up the neck muscles before usage was the most prominent predictors of neck disability.